THE DILATATION OF BRAIN VENTRICLE DUE TO CONGENITAL TOXOPLASMOSIS IN MICE CORRELATED WITH APOPTOSIS BUT NOT WITH TRANSFORMING GROWTH FACTOR BETA - Lucia Tri Suwanti; Mufasirin Mufasirin; Hani Plumeriastuti (Universitas Syiah Kuala, 2018)
This study aimed to determine the occurences of mice brain ventricles dilatation that congenitally infected with Toxoplasma gondii (T. gondii) as a marker of hydrocephalus and cellular changes in the brain. A total of twenty pregnant mice (11.5 days pregnacy) were divided into 2 groups, which were control (P1) group and treatment (P2) group. The mice in the treatment group were infected with 101 tachyzoites of T. gondii. All mice were maintained until delivery. The newborn mice were sacrificed and their brain were removed and fixed in 10% buffered formalin to prepare histology slides with HE staining for observation of ventricular width, TUNEL assay for apoptosis observation, and immunohistochemistry for the expression of transforming growth factor beta (TGF-β) observations. The data were analyzed using t test and linear regression. The results showed that ventricular width and apoptosis index significantly increased (P0.01) in the treatment group compared to control group, but there was no difference in the expression of TGF-β (P0.05) in both groups. Dilatation of ventricle correlated with the apoptotic index of brain cells but did not correlated with the expression of TGF-β.